ROMANIAN LEGISLATION IN THE HEALTHCARE SERVICES DOMAIN - LAZEA, Ruxandra; MUREȘAN, Maria (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 17 (2015): Annales Universitatis Apulensis Series Oeconomica, 2015)
The current research study aims to reflect some of the operating modes of the Romanian healthcare system, which seem to have remained unchanged in the last 30 years. A general background of the medical system will bring into play principles such as: society responsibility for the public health, multidisciplinary approach, decentralization of the public health system or an integrated informational and computerized system for the public heath management. Two important dimensions we considered to be the most relevant have been highlighted in our paper, namely, the patients’ rights and obligations and accessibility to medical services, as well.